Phenotypic response of wheat under application of combinations of herbicides and nitrogen - Carvalho, Ivan Ricardo; Cazarotto, Matheus Silva; Loro, Murilo Vieira; Pradebon, Leonardo Cesar; Bruinsma, Gabriel Mathias Weimer; Roza, João Pedro Dalla; Uhde, Leonir Terezinha (Revista de Ciências Agroveterinárias, 2025)
The objective of this work was to evaluate the phenotypic response of wheat plants to combinations of herbicides and nitrogen fertilization. The study was carried in the municipality of Augusto Pestana - RS. The experimental design used was randomized blocks, with 19 treatments being evaluated, in 16 replications. The analysis of variance was carried out at 5% probability using the F Test. Afterwards, the Student-Newman-Keuls mean comparison test was used at the 5% probability level. The main components analysis was carried out using Biplot. Pearson's linear correlation coefficients were calculated between pairs of characters, with significance imposed by the Student's t test at 5% probability. The average Euclidean distance was calculated and grouping was performed using the UPGMA method. To express the best assertiveness in wheat yield, regression tree was used, defining grain yield as the dependent variable and the other variables as independent. The application of 1500 ml 2,4-D + 250 ml Clodinafop-propargyl + 100 kg urea reduces spike viability, spike harvest index and spikelet arrangement index in the wheat spike. In wheat, the number of grains in the wheat spike is not influenced by the interaction between herbicides and nitrogen.